Legendre Wavelets Method for Solving Fractional Population Growth Model in a Closed System. (30th September 2013) - Heydari, M. H.; Hooshmandasl, M. R.; Cattani, C.; Li, Ming
Abstract : A new operational matrix of fractional order integration for Legendre wavelets is derived. Block pulse functions and collocation method are employed to derive a general procedure for forming this matrix. Moreover, a computational method based on wavelet expansion together with this operational matrix is proposed to obtain approximate solution of the fractional population growth model of a species within a closed system. The main characteristic of the new approach is to convert the problem under study to a nonlinear algebraic equation.